2019
DOI: 10.1002/jcb.28285
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circ‐PRKCI functions as a competitive endogenous RNA to regulate AKT3 expression by sponging miR‐3680‐3p in esophageal squamous cell carcinoma

Abstract: Circular RNA (circRNA) is a new noncoding RNAs and plays an important role in many pathological processes. Recently, studies have shown that circular RNA_PRKCI (circ-PRKCI) regulates cell proliferation and cell migration of tumor cells. Esophageal carcinoma is a highly malignant digestive tract tumor, which is divided into esophageal adenocarcinoma and esophageal squamous cell carcinoma. In this study, we studied whether circ-PRKCI might influence cell proliferation and cell migration in esophageal squamous ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…28,29 For instance, circ_0006528 facilitates human breast cancer progression by activating the MAPK/ERK signaling pathway 30 ; circ_ 0058124 modulates the carcinogenesis and invasion of NOTCH3/GATAD2A papillary thyroid carcinoma with high expression linked to adverse pathological parameters in patients, 31 and circ-PRKCI enhances the proliferation and invasion of ESCC via upregulating AKT3 expression. 32 In this study, we demonstrated that compared with normal tissues, circ_0000654 expression in ESCC tissues was remarkably increased, and its high expression was linked to the higher T stage and lymph node metastasis of ESCC patients. These results reveal that circ_0000654 is expected to be a new biomarker for evaluating the prognosis of ESCC patients.…”
Section: Discussionmentioning
confidence: 71%
“…28,29 For instance, circ_0006528 facilitates human breast cancer progression by activating the MAPK/ERK signaling pathway 30 ; circ_ 0058124 modulates the carcinogenesis and invasion of NOTCH3/GATAD2A papillary thyroid carcinoma with high expression linked to adverse pathological parameters in patients, 31 and circ-PRKCI enhances the proliferation and invasion of ESCC via upregulating AKT3 expression. 32 In this study, we demonstrated that compared with normal tissues, circ_0000654 expression in ESCC tissues was remarkably increased, and its high expression was linked to the higher T stage and lymph node metastasis of ESCC patients. These results reveal that circ_0000654 is expected to be a new biomarker for evaluating the prognosis of ESCC patients.…”
Section: Discussionmentioning
confidence: 71%
“…Overexpression plasmid or small interfering miRNA mimics and inhibitors are commonly used for transient overexpression or knockdown of miRNAs in ESCC cells [34,52,107]. RNA interference (RNAi), mainly involving siRNA and short hairpin RNA (shRNA), has been widely applied in knockdown of ncRNAs in ESCC cells [18,27,31,80]. However, the effectiveness of overexpression plasmid, siRNAs, miRNA mimics, and inhibitors is limited.…”
Section: Experimental Approaches Of Studying Non-coding Rnas In Esccmentioning
confidence: 99%
“…The biological functions of circRNAs have mainly been reported as miRNA sponging and transcription regulation [25,26]. These characteristics and functions of circRNAs have contributed to its roles in the biology of human cancers, including ESCC [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with paracancerous tissues, the expressions of hsa_circ_0067934, circFNDC3B, circ-TTC17, hsa_circ_0006168, circPVT1 and hsa_circ_100873 were significantly up-regulated in EC tissues [39,40,42,43,56,57]. So far, cir-ITCH, circ-PRKCI, circRAD23B, cZNF292, circ-Foxo3, circGSK3 β, circLARP4 and hsa_ circ_0004771 have been shown to regulate the proliferation and apoptosis of EC cells through different signal pathways [35,37,50,[58][59][60][61][62]. In a word, different results suggest that circRNAs may promote or inhibit development of EC through different mechanisms (Fig.…”
Section: Regulation Of Circrna On Proliferation Migration Invasion mentioning
confidence: 88%